2019
DOI: 10.1111/1750-3841.14963
|View full text |Cite
|
Sign up to set email alerts
|

Study on Antioxidant Activity of Amino Acids at Frying Temperatures and Their Interaction with Rosemary Extract, Green Tea Extract, and Ascorbic Acid

Abstract: Some amino acids have strong antioxidant activity in frying oil. This study aimed to obtain further information including antioxidant activity at different concentrations and interactions with rosemary extract, green tea extract, and ascorbic acid. Antioxidant activity of arginine, cysteine, lysine, methionine, and tryptophan was examined by increasing the concentration in soybean oil (SBO) at 180°C within the concentration range of 0 to 15 mM. These amino acids showed increased activity with increasing concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Glutamic acid and histidine decreased the generation of the hydroxyl radicals [ 52 ]. Hwang et al demonstrated a strong antioxidant activity of methionine and lysine [ 53 ]. The results of Tian et al showed that the electronic and hydrogen-bonding properties of the amino acids in the tripeptide sequences, and the steric properties of the amino acid residues at the C- and N-termini, play a major role in the antioxidant activities of the tripeptides.…”
Section: Discussionmentioning
confidence: 99%
“…Glutamic acid and histidine decreased the generation of the hydroxyl radicals [ 52 ]. Hwang et al demonstrated a strong antioxidant activity of methionine and lysine [ 53 ]. The results of Tian et al showed that the electronic and hydrogen-bonding properties of the amino acids in the tripeptide sequences, and the steric properties of the amino acid residues at the C- and N-termini, play a major role in the antioxidant activities of the tripeptides.…”
Section: Discussionmentioning
confidence: 99%
“…The rosemary samples extracted at 60 • C were prepared as per the method of Hwang et al [23]. Each of the defatted samples (200 mg) were weighed into a glass ampoule and 5 mL of 6N HCl was added.…”
Section: Determination Of Amino Acid Contentmentioning
confidence: 99%
“…Amino acids have also been shown to produce a synergistic effect with tocopherol which improves antioxidant activity [ 76 ]. Synergistic effects of methionine with epigallocatechin gallate (EGCG) and ascorbic acid have also been reported [ 77 ]. GABA can act as signaling molecules and exhibits reactive oxygen species (ROS) scavenging activity [ 78 ].…”
Section: Resultsmentioning
confidence: 99%